Recuperamos información y narramos anécdotas - Anticona Cabrera, Maritza Yaseni (2019)
The present work of pedagogical sufficiency is basically oriented to develop in students their abilities to learn to understand oral texts from the development of methodological strategies related to the recovery of information in oral texts: the story, based on the use of expressions as figurative sense, vocabulary that includes synonyms and terms of the fields of knowledge._x000D_ The learning session called “We retrieve information, telling anecdotes”, is designed to meet the standards of the fourth grade of primary education of the Educational Institution “María del Carmen” from the district of “El Porvenir”, in its elaboration the use of pedagogical processes of the problematization, motivation, recovery of previous knowledge, purpose and organization, management and accompaniment for the development of skills and the evaluation of learning, as well as the didactic processes of the communication area related to the previous, during and after listening of oral texts , in order to promote the active and committed participation of students in the construction of meaningful learning, using as a tool the checklist for collecting valid and reliable information.